2002
DOI: 10.1159/000066470
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Pulmonary Aspergillosis

Abstract: Background: Invasive pulmonary aspergillosis usually occurs in immunocompromised patients. Mild abnormality of host defence is usually present in the chronic necrotising form of the disease. Acute aspergillus pneumonia usually affects patients who are seriously immunocompromised. Objectives: The purpose of the study was to highlight the possibility of occurrence of invasive pulmonary aspergillosis also in patients with mild abnormality of host defence. Methods: In a retrospective study 6 patients were analysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 15 publications
(17 reference statements)
0
2
2
Order By: Relevance
“…It is shown that A. fumigatus CF expressed a high cytotoxicity on murine macrophages under highly aerated conditions 32. However, in our study cytotoxic effect was expressed by CFs obtained on day 6 and condition with 20% O 2 , while other study showed cytotoxicity with A. fumigatus CF obtained after 15 h 32. The samples obtained during short-term fermentation (day 1 and 3) did not express a significant cytotoxicity in this study.…”
Section: Disscusioncontrasting
confidence: 82%
See 1 more Smart Citation
“…It is shown that A. fumigatus CF expressed a high cytotoxicity on murine macrophages under highly aerated conditions 32. However, in our study cytotoxic effect was expressed by CFs obtained on day 6 and condition with 20% O 2 , while other study showed cytotoxicity with A. fumigatus CF obtained after 15 h 32. The samples obtained during short-term fermentation (day 1 and 3) did not express a significant cytotoxicity in this study.…”
Section: Disscusioncontrasting
confidence: 82%
“…Our data demonstrated significant inhibition of cell proliferation when extracts after prolonged aerated conditions were used ( A. fumigatus CF AE6) (Figure 2). It is shown that A. fumigatus CF expressed a high cytotoxicity on murine macrophages under highly aerated conditions 32. However, in our study cytotoxic effect was expressed by CFs obtained on day 6 and condition with 20% O 2 , while other study showed cytotoxicity with A. fumigatus CF obtained after 15 h 32.…”
Section: Disscusioncontrasting
confidence: 79%
“…However, the diagnosis of IPA can only be confirmed by histological determination of invasion of lung tissue by Aspergillus species or presence of positive cultures for Aspergillus in a sample obtained from a sterile site by an invasive procedure e.g. lung biopsy ( Kristan et al 2002 ; Ascioglu et al 2002 ; Maertens et al 2004). Open lung biopsy has very low morbidity and is recommended to establish the diagnosis of IPA.…”
Section: Discussionmentioning
confidence: 99%
“…Aspergillosis refers to infectious diseases caused by fungi of the genus Aspergillus present in the residential environment, such as the soil and air (1). Invasive pulmonary aspergillosis (IPA) can be a life-threatening infectious disease for immunosuppressed patients receiving chemotherapy or recipients of stem cell transplantation (2). Early diagnosis is very challenging because IPA has similar clinical features to the usual respiratory infections (3).…”
mentioning
confidence: 99%